Mobile health service demand, key morbidity magnitude, and trend at mountainous outreaches of Uttarakhand: A descriptive study - Roy, Debabrata; Dobhal, Priyanka; Deep Shikha; Sinha, Richa; Das, Sai Chandan (Asian Journal of Medical Sciences, 2023)
Background: Deploying mobile health vans (MHVs) to service disadvantaged, underserved mountainous hamlets across six districts of Uttarakhand on a “fixed day-fixed location” strategy was an effective initiative in the state in collaboration with Technology Information Forecasting and Assessment Council (TIFAC) and NRHM. Aims and Objectives: The aim of the study was to provide quality diagnostic and curative care through mobile health clinics at select mountainous outreaches of Uttarakhand state. Materials and Methods: A bimonthly mobile health services with fully equipped MHV sponsored by the directorate of science and TIFAC and assessment council and Government of Uttarakhand on a “fixed day, fixed time and fixed place” schedule were provided along pre-designated service locations. Results: A total of 77,688 beneficiaries received services through 902 camps spanning 13 quarters with an estimated 5976 and 89 beneficiaries per quarter per camp; 573 clients received ultrasound, 639 X-ray, 34 ECG, and 3543 other lab procedures. Quarterly demand for services was highest, 19.5% for gastrointestinal disorders, followed by 18.4% for musculoskeletal disorders, 13.8% for genitourinary system disorders, 11.8% for respiratory system disorders, and 8.5% for ENT and ocular disorders. The prevalent morbidity was predominantly acid peptic disease (15.5%), followed by osteoarthritis (13.3%) and low backache and renal stones (7.2% each). Conclusion: Integrating mobile health service delivery component with existing strategies adopted by public health system in primary health care is an operationally feasible and viable option to address ‘inaccessibility at disadvantaged mountainous outreach.